Le discours du pathétique pour la quête de la solitude dans les confessions, les dialogues et les rêveries du promeneur solitaire de Jean-Jacques Rousseau - Abdou Ndiaye (Multilinguales)
There is in the author of walks, Confessions, Émile and Nouvelle Héloïse a special relationship that he maintains with writing which seems to function as a place of memory where the persecuted can recharge their batteries, a favorable place to redemption and a sure shield against attacks of all kinds, even those of his own desires. Thus, in the search for his identity, several possibilities are open to him to find the stability of the ego and which lie in scriptural manipulation. In the face of attacks from his enemies, how Rousseau sets himself up as a victim? This paper is a critical study of Rousseau’s autobiographical works. Its role is to show how this author uses his creative verb to entice the reader with feelings. Thus in the face of suffering, the flight of time which leads to its future decline, we will show how the elegy, the inner song and the emotion of the style will take charge of transforming the attacks of its detractors into energies bringing it closer to its reader.